English

If y is the mean proportional between x and z, prove that: x2-y2+z2x-2-y-2+z-2=y4. - Mathematics

Advertisements
Advertisements

Question

If y is the mean proportional between x and z, prove that: `(x^2 - y^2 + z^2)/(x^(-2) - y^(-2) + z^(-2)) = y^4`.

Sum

Solution

Given, y is the mean proportional between x and z.

`=>` y2 = xz

L.H.S = `(x^2 - y^2 + z^2)/(x^(-2) - y^(-2) + z^(-2))`

= `(x^2 - y^2 + z^2)/(1/x^2 - 1/y^2 + 1/z^2)`

= `(x^2 - xz + z^2)/(1/x^2 - 1/(xz) + 1/z^2)`

= `(x^2 - xz + z^2)/((z^2 - xz + x^2)/(x^2z^2))`

= x2z2

= (xz)2

= (y2)2   ...(∴ y2 = xz)

= y4

= R.H.S

shaalaa.com
  Is there an error in this question or solution?
Chapter 7: Ratio and Proportion (Including Properties and Uses) - Exercise 7 (B) [Page 94]

APPEARS IN

Selina Mathematics [English] Class 10 ICSE
Chapter 7 Ratio and Proportion (Including Properties and Uses)
Exercise 7 (B) | Q 12 | Page 94
Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×